КЕРУВАННЯ ВХІДНОЮ РЕАКТИВНОЮ ПОТУЖНІСТЮ МАТРИЧНИХ ПЕРЕТВОРЮВАЧІВ - Михальський , В.М.; Соболєв , В.М.; Чопик , В.В.; Шаповал , І.А. (Інститут електродинаміки НАН України, Київ, 2014)
Features of the matrix converter control with maximum achievable range of the input reactive power for the specified operating point are considered. Generalized analysis based on a vector representation of switching functions has been carried out. The corresponding modulation strategy and algorithm of the direct control of the input reactive power by setting the space vector components of the control functions while maintaining the greatest possible range of output voltage regulation have been proposed. The paper presents an approach that formalizes and facilitates the process of forming the matrix of the matrix converter control functions. This is achieved through the direct reference of the desired transfer coefficient with respect to the reactive component of the input current of the matrix converter and definition of the necessary for the implementation of this zero sequence component coefficient of the control functions. The simulation results are presented. References 11, figures 7.